Pendampingan Digital Marketing Pada Pelaku UMKM Nila Oscar di Desa Jatimekar Jatiluhur Purwakarta - Siti Nurjanah, Riski; Pratiwi, Dhita Fitriani; Mendrofa, Roni Sahputra; Oktapianti, Milasari (STIE Syariah Indonesia Purwakarta, 2022)
Micro, Small and Medium Enterprises (MSMEs) always experience challenges, but this is not an obstacle for MSMEs to develop their business even further. The effect of digital use which is growing well has a positive influence on the development of MSMEs in terms of marketing. The aim of the community service program (PKM) is to help digital-based marketing of Nila Oscar MSME products in Jatimekar Jatiluhur Village, Purwakarta. This PKM method uses a training and mentoring approach. The results of the community service program regarding Digital marketing Assistance for Oscar Tilapia MSME Actors in Jatiluhur Village Jatimekar Jatiluhur Purwakarta which was carried out by the PKM Team through several stages, technically it had gone well and on schedule. The Digital marketing Assistance activities are highly anticipated by Oscar Tilapia MSME actors, because they hope that this assistance program can increase the amount of Salted Fish MSME production. In addition, this assistance provides a new color in the marketing process for Tilapia Oscar MSME actors in Jatiluhur Village, Jatiluhur, Purwakarta, who usually use traditional methods, now can do Digital marketing.